Nest-site fidelity in Red-tailed Tropicbirds informs costing a localised ant baiting strategy at Ashmore Reef. (2nd July 2020) - Mott, Rowan; Hodgson, Jarrod C.; Herrod, Ashley; Clarke, Rohan H.
ABSTRACT: In many animal species, individuals re-use the breeding site they used in the previous breeding season. Consequently, they accrue benefits including reduced time searching for a territory, and enhanced predator avoidance. Many seabirds display high levels of nest-site fidelity. We sought to determine whether nest-site fidelity occurs in Red-tailed Tropicbirds ( Phaethon rubricauda ) breeding at Ashmore Reef (eastern Indian Ocean) by recording the nest location of individually-marked birds across three years (2012–2014). We found that Red-tailed Tropicbirds at this surface-nesting colony were highly faithful to their previous nest-site, with a median distance between successive nests of just 13.4 m. By using digitised vegetation maps for Ashmore Reef, we provide quantitative evidence that Red-tailed Tropicbird nest-site fidelity is not driven by a lack of suitable vegetated sites. These findings have important management implications because breeding success at this small, regionally-significant Red-tailed Tropicbird colony is negatively affected by an invasive species, the tropical fire ant ( Solenopsis geminata ). Using localised ant baiting around known Red-tailed Tropicbird nest-sites may confer benefits on current and future tropicbird breeding attempts. We estimated the financial cost per treatment to bait the 0.85 ha within 13.4 m of known Red-tailed Tropicbird nest-sites, an area expected to encompass half of all subsequent breeding attempts, to be low. This represents a cost-effective interim management strategy prior to any island-wide eradication programme. Therefore, we recommend localised ant baiting around tropicbird nests within an adaptive management framework such that optimum baiting parameters can be resolved (e.g., baiting frequency, most effective baiting radius).